Social Innovation of Tourism Village: Asset-based Community Development in East Rombiya Village, Madura, Indonesia - Salam, Abdus; Sihidi, Iradhad Taqwa; Akmalia, Naila Febrina; Hardini, Hevi Kurnia (JSW (Jurnal Sosiologi Walisongo), 2025)
East Rombiya Village, Sumenep, Madura, is a compelling example of a region actively advancing sustainable village tourism by leveraging its local potential. This study aims to analyze the social innovation initiated by the Village Government through the Village-owned Enterprises (BUMDes) in developing the "Somber Rajeh" tourist destination using an Asset-based Community Development (ABCD) approach, and its impact on community empowerment and the village economy. The research method used is qualitative, with data collection through observation, in-depth interviews, and documentation involving the village government, BUMDes managers, and the local community. The results show that the implemented social innovation successfully transformed natural springs into sustainable tourist attractions, created new jobs, increased the village's local income, and strengthened community participation in tourism management. The analysis reveals that synergy among the village government, BUMDes, and the local community is the critical success factor of inclusive and independent tourism development. This study suggests that local assets can be leveraged to generate effective solutions for sustainable village development, grounded in community empowerment.